The pathogenic role of connective tissue growth factor in osteoarthritis. Issue 7 (19th July 2019) - Tu, Min; Yao, Yao; Qiao, Feng Hua; Wang, Li
Abstract : Osteoarthritis (OA) is the most common form of arthritis, and connective tissue growth factor (CTGF) is found to be up-regulated in adjacent areas of cartilage surface damage. CTGF is present in osteophytes of late stage OA. In the present study, we have reviewed association of CTGF in the development and progression of OA and the potential effects of CTGF as a therapeutic agent for the treatment of OA. We have reviewed the recent articles on CTGF and OA in databases like PubMed, google scholar, and SCOPUS and collected the information for the articles. CTGF is usually up-regulated in synovial fluid of OA that stimulates the production of inflammatory cytokines. CTGF also activates nuclear factor-κB, increases the production of chemokines and cytokines, and up-regulates matrix metalloproteinases-3 (MMP-3) that in turn leads to the reduction in proteoglycan contents in joint cartilage. Consequently, cartilage homeostasis is imbalanced that might contribute to the pathogenesis of OA by developing synovial inflammation and cartilage degradation. CTGF might serve as a useful biomarker for the prognosis and treatment of OA, and recent studies have taken attempt to use CTGF as therapeutic target of OA. However, more investigations with clinical trials are necessary to validate the possibility of use of CTGF as a biomarker in OA diagnosis and therapeutic target for OA treatment.